COMPARATIVE LIFE CYCLE ASSESSMENT OF EDTA-MODIFIED AND AMINE GRAPTHED SILICA XEROGELS - Kartini Megasari; Andri Saputra; Ari Nur Chintia (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2022)
COMPARATIVE LIFE CYCLE ASSESSMENT OF EDTA-MODIFIED AND AMINE GRAPTHED SILICA XEROGELS. NaI-131 removal from hospital wastewater using various silica xerogel adsorbents has been studied in order to meet the clearance level of radioactive waste. The contaminants emitted from the adsorbent manufacturing may affect the environment and human health. This study aimed to assess and minimize the environmental impacts of two adsorbents: EDTA-modified xerogel silica (EDTA Si-Xe) and Amine grafted silica xerogels (Amine Si-Xe), utilizing life cycle assessment (LCA) with the cradle to gate approach. OpenLCA 1.7 was used to estimate the impact, where background data were acquired from the European reference Life Cycle Database (ELCD) 3.2. The results show the dominant environmental impact resulting from adsorbent manufacturing is climate change. The impact of climate change on EDTA Si-Xe manufacturing and Amine Si-Xe manufacturing is about 0.510 CO2-eq and 0.258 CO2-eq, respectively. EDTA Si-Xe manufacturing performed the best (lower environmental impact) compare to Amine Si-Xe manufacturing. The process stage that contributes dominantly to environmental impact is calcination which gives high environmental impacts to climate change. The percent contribution of calcination to the environmental impact on EDTA Si-Xe manufacturing and Amine Si-Xe manufacturing is about 87% and 66%, respectively. The environmental impacts of the adsorbents manufacturing especially in climate change can be reduced by using Capture Carbon Storage (CCS) technology. Improvement analysis shows EDTA Si-Xe performed lower environmental impact compare to Amine Si-Xe with the value of impact categories lower than without applied CCS technology, especially value of climate change.